2019
DOI: 10.1002/jgm.3093
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in IL1R1 and IL1R2 are associated with susceptibility to thyroid cancer in the Chinese Han population

Abstract: Background Thyroid carcinoma accounts for a large part of endocrine neoplasia and the relationship between inflammation and thyroid cancer has been validated previously. Two known receptors of interleukin (IL)‐1, IL‐1 receptor 1 (IL1R1) and IL‐1 receptor 2 (IL1R2), are implicated in numerous inflammatory responses. The present study aimed to assess the genetic polymorphisms of IL1R1 and IL1R2 with respect to thyroid cancer in the Chinese Han population. Methods Eleven single nucleotide polymorphisms of IL1R1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…This could be potentially beneficial for the treatment of immune-related diseases. [27,28] In the process of ischemic stroke, inflammatory response plays an important role in the development of brain injury. Related studies have shown that IL-1 family of cytokine and receptors may play a role in the pathogenesis of ischemic cerebral apoplexy.…”
Section: Discussionmentioning
confidence: 99%
“…This could be potentially beneficial for the treatment of immune-related diseases. [27,28] In the process of ischemic stroke, inflammatory response plays an important role in the development of brain injury. Related studies have shown that IL-1 family of cytokine and receptors may play a role in the pathogenesis of ischemic cerebral apoplexy.…”
Section: Discussionmentioning
confidence: 99%
“…IL1R1 is a cytokine receptor that belongs to the IL-1 receptor family, and is available to modulate cell metabolism and multiple cytokine-induced immune inflammatory responses [ 31 ]. IL1R1 exerts a critical role in LEDVT and its expression could be modulated by miRNA [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid cells synthesize several cytokines, including IL-1, IL-6, IL-8, IL-12, IL-13, and IL-15 (21). The IL-1 family consists of IL-1α, IL-1β, and two receptors, IL-1 receptor 1 (IL1R1) and IL-1 receptor 2 (IL1R2); these receptors are found to be associated with thyroid carcinogenesis (22). IL-1β is found to be produced in the thyroid gland of HT patients by infiltrating monocytes and macrophages, activated endothelium, fibroblasts, and thyrocytes.…”
Section: Discussionmentioning
confidence: 99%